Simulating Marine New Particle Formation and Growth Using the M7 Modal Aerosol Dynamics Modal - Ciaran Monahan; Henri Vuollekoski; Markku Kulmala; Colin O'Dowd (Advances in Meteorology)
A modal atmospheric aerosol model (M7) is evaluated in terms of predicting marine new particle formation and growth. Simulations were carried out for three different nucleation schemes involving (1) kinetic self-nucleation of OIO (2) nucleation via OIO activation by H2SO4 and (3) nucleation via OIO activation by H2SO4 plus condensation of a low-volatility organic vapour. Peak OIO and H2SO4 vapour concentrations were both limited to 6×106 molecules cm-3 at noontime while the peak organic vapour concentration was limited to 12×106 molecules cm-3. All simulations produced significant concentrations of new particles in the Aitken mode. From a base case particle concentration of 222 cm-3 at radii >15 nm, increases in concentrations to 366 cm-3 were predicted from the OIO-OIO case, 722 cm-3 for the OIO-H2SO4 case, and 1584 cm-3 for the OIO-H2SO4 case with additional condensing organic vapours. The results indicate that open ocean new particle production is feasible for clean conditions; however, new particle production becomes most significant when an additional condensable organic vapour is available to grow the newly formed particles to larger sizes. Comparison to sectional model for a typical case study demonstrated good agreement and the validity of using the modal model.